HUBUNGAN STATUS NUTRISI DENGAN NYERI MENSTRUASI PADA REMAJA SMP NEGERI 16 BANDUNG - Marfuah, Dewi; Mayasari, Rita (Journal of Holistic Nursing Science, 2018)
Influenced by nutritional status. The prevalence of nutritional status in Indonesia by 32.6% malnourished and 25.6% excess nutrients. If there is nutritional status disorders will aggravate the menstrual pain. Purpose: This study was conducted to determine the relationship of nutritional status in adolescents whose having dysmenorrhea in SMP Negeri 16 Bandung. Methods: Using a correlational descriptive design with cross sectional approach as well as using non-random sampling techniques, the number of population in this study of 50 female students who experience dysmenorrhea and the number of samples of 39 respondents. Data were analyzed using the Spearman test. Results: Based on the statistical analysis, mostly the respondents have malnutrition about 19 respondents (41.7%) and they have more likely a mild pain during menstrual period at about 22 respondents (56, 4%). The Spearman test results show that the value between the nutritional status with menstrual pain p-value of 0.039 (p<0.05) and the coefficient of contingency -0.332. Conclusion: There is a relationship between the nutritional status with dysmenorrhea. Suggestion: It is expected that it is able to give any appropriate feedback toward nursing process in anticipacing any reproduction health such as a clear information about nutritional status which is contributing a lot to have severe pain during menstrual period among adolescents.